An examination of video assisted leisure education in middle-aged and older adults. (15th March 2021) - Dattilo, John; Lorek, Amy; Sliwinski, Martin; Chen, Shang-Ti; Hill, Nikki
Abstract: Using a quasi-experimental pretest-post-test design without a control group we examined effects of leisure education, Project BHEL: Be Healthy and Enjoy Leisure, consisting of seven 1-hour sessions using instructional videos, discussions, and workbook activities to help older adults set goals, design a plan to increase their leisure satisfaction, and problem-solve ways to overcome barriers to goal achievement. The intervention was conducted across four locations with 89 adults ( M = 74 years-old, range 58–94). Participants' satisfaction with leisure was significantly higher post-compared to pre-intervention. There was a significant increase on knowledge of leisure assessment and, though scores remained low post-intervention, overall scores almost doubled from pre-intervention. Reported frequency of leisure participation significantly increased between pretest and follow-up. Participants consistently rated their goal achievement and their program satisfaction highly. Overall, findings indicate that Project BHEL increased engagement in, and satisfaction with aspects of leisure.